Supplementing fructose-based block supplements to forage-fed cattle increases capacity for lactic acid metabolism - K.A. Miller; M.J. Quinn; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2010)
Acidosis is one of the more important maladies afflicting cattle fed significant amounts of grain and has enormous economic impact for feedlots, dairies, and producers of seed stock. The highest incidence of acidosis occurs when animals are being transitioned from high-roughage diets to diets containing high levels of concentrates. When grain-based diets are consumed in excess, consumed too quickly, or fed without proper adaptation, digestive end products (organic acids) can accumulate within the rumen, resulting in acidosis. Lactic acid is one of the key organic compounds that accumulates under these conditions. Coupled with the animal's limited ability to metabolize lactate, accumulation of lactic acid in the rumen lowers ruminal pH and subsequently depresses feed intake. One means of preventing acidosis is to directly populate the rumen with lactate-utilizing bacteria. Alternatively, exposure to low levels of lactate (i.e., levels insufficient to harm the animal) may stimulate development of a population of lactate-utilizing bacteria. The objective of our study was to determine if supplementing low-moisture blocks made of high fructose corn syrup could increase ruminal lactate concentrations and subsequently stimulate growth of lactate-metabolizing bacteria. If successful, this could prove useful for adapting forage-fed cattle to grain-based diets.
Keywords: Cattlemen' s Day; 2010; Kansas Agricultural Experiment Station contribution; no. 10-170-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1029; Beef Cattle Research; 2010 is known as Cattlemen' s Day; Beef; Fructose; Lactic acid; Roughage